Electronic and magnetic properties of ferrous iron in a true square-planar molecular environment - Diederich, Tim; Wehland, Tim; Schrodt, Maximilian; Kochetov, Nikolai; Schnegg, Alexander; JimenezMuñoz, Carlos; Krewald, Vera; Ni, Lingmei; Salas, Nicole Segura; Kramm, Ulrike; Ballmann, Joachim; Enders, Markus (Chemistry a European journal, 2025)
The electronic and magnetic properties of ferrous iron in the iron(II)-2,3,9,10,16,17,23,24-octakis(2,6-diisopropylphenoxy)phthalocyanine (FePcOAr), exhibiting a true square-planar molecular environment, are investigated. Inhibition of intermolecular interactions by steric substituents allows detailed investigation of the electronic structure arising from the planar geometry of the d6 electron configuration. Complementary magnetometry, Mössbauer, FD-FT THz-EPR (frequency-domain Fourier-transform terahertz electron paramagnetic resonance) and pNMR (nuclear magnetic resonance of paramagnetic molecules) spectroscopies show that FePcOAr has an S = 1 ground state with large positive axial zero-field splitting (ZFS) and a strongly anisotropic g-tensor, with two g-values much larger than the free electron g-value and one smaller. Correlation between the magnetic properties and the electronic structure is provided by high-level quantum chemical calculations. The calculations indicate a nearly triply degenerate ground level, in which spin-orbit coupling mixes the isolated 3A2g ground state with two excited 3Eg states, whose energy gaps to the ground state are almost identical. These findings provide valuable insights in the electronic structure of iron phthalocyanines and the long-standing discussion on their true electronic ground level, which has important implications for the application of this important class of complexes in catalysis and magnetic materials.
Zuerst veröffentlicht: 28. Mai 2025
Gesehen am 16.10.2025